2013
DOI: 10.7231/jon.2013.24.spc1.055
|View full text |Cite
|
Sign up to set email alerts
|

The Study on the Difference of EEG Results between Anger Syndrom and Major Depressive Disorder

Abstract: We will discuss the differences on EEG results of Post-traumatic embitterment disorder (PTED) and Major depressive disorder (MDD). Methods : We measured EEG on 21 sites (Fp1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Previous EEG studies have demonstrated that the brain waves of subjects with MDD differ significantly from those without MDD. There are distinguishable patterns in resting EEG waves between MDD and non-MDD subjects, and activation of the prefrontal alpha waves is more prominent in the left hemisphere than in the right in patients with MDD [38, 39]. The EEG records obtained in this study will be analyzed with a focus on the balance of prefrontal alpha waves between the right and left hemispheres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous EEG studies have demonstrated that the brain waves of subjects with MDD differ significantly from those without MDD. There are distinguishable patterns in resting EEG waves between MDD and non-MDD subjects, and activation of the prefrontal alpha waves is more prominent in the left hemisphere than in the right in patients with MDD [38, 39]. The EEG records obtained in this study will be analyzed with a focus on the balance of prefrontal alpha waves between the right and left hemispheres.…”
Section: Discussionmentioning
confidence: 99%
“…Electrodes will be attached at two sites (F3, F4) out of the 10–20-site system of the scalp to evaluate the balance of prefrontal alpha waves from the right and left hemispheres. Previous EEG studies have confirmed that a characteristic, asymmetric pattern of resting frontal activity can be observed in people with MDD that is unlike measurements made in the non-MDD population [38, 39]. …”
Section: Methodsmentioning
confidence: 99%